Peran Budaya Organisasi sebagai Keunggulan Bersaing dalam Proses Manajemen Strategis dan Performansi (Sebuah Tinjauan dari Resoruce-Based View) - Jahja Hamdani Widjaja (Jurnal Manajemen Maranatha, 2010)
Strategic management studies want to find how a firm gains its sustainable competitive advantage. Organization culture may provide a source of sustainable competitive advantage. Organization culture also has some influences in the strategic management process. But, there are only limited studies to explore the relationship between organizational cultrue and the management strategic process within a firm. This literature study aims to seek a good fit between a specific type of organizational culture and a specific type of strategic management model. By using the Competing Value Framework, I draw the relationship between organizational culture typology and the appropriate strategic management model.Keywords: budaya organisasi, resource-based view, model manajemen strategis, performansi perusahaan